2014
DOI: 10.1089/acm.2013.0329
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use in Infertility: Cultural and Religious Influences in a Multicultural Canadian Setting

Abstract: Objectives: To explore the use of complementary and alternative medicine (CAM) for infertility in a multicultural healthcare setting and to compare Western and non-Western infertility patients' reasons for using CAM and the meanings they attribute to CAM use. Design: Qualitative semi-structured interviews using thematic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…This prevalence of herbal medicine use is lower than similar studies conducted in Uganda [ 38 ] and Lebanon [ 35 ] but higher than studies conducted in USA [ 36 ], Turkey [ 37 ], Jordan [ 33 ], Australia [ 42 ], and Rwanda [ 39 ]. The difference in utilization rate observed with other countries may be partly due to variation in the availability and access to conventional healthcare and the sociocultural difference on how traditional, complementary, and alternative medicine use is perceived as well as the heterogeneity in the study design and definition of TCAM therapy used [ 45 , 46 ]. Considering the widespread use of herbal medicine among the Sierra Leonean populace [ 47 , 48 ], and the fact that women in Africa are under enormous pressure to conceive [ 5 , 49 ], the search for answers to their predicament goes beyond seeking conventional care to also include alternative medical care in the form of herbal medicine [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence of herbal medicine use is lower than similar studies conducted in Uganda [ 38 ] and Lebanon [ 35 ] but higher than studies conducted in USA [ 36 ], Turkey [ 37 ], Jordan [ 33 ], Australia [ 42 ], and Rwanda [ 39 ]. The difference in utilization rate observed with other countries may be partly due to variation in the availability and access to conventional healthcare and the sociocultural difference on how traditional, complementary, and alternative medicine use is perceived as well as the heterogeneity in the study design and definition of TCAM therapy used [ 45 , 46 ]. Considering the widespread use of herbal medicine among the Sierra Leonean populace [ 47 , 48 ], and the fact that women in Africa are under enormous pressure to conceive [ 5 , 49 ], the search for answers to their predicament goes beyond seeking conventional care to also include alternative medical care in the form of herbal medicine [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been an increase in the use of CAM use over time [ 25 ], despite the fact that this increase is not necessarily supported by empirical evidence. However, some individuals may choose to use CAM methods to feel more in control of their fertility treatment [ 5 ]. This potential feeling of empowerment, however, is not adequately captured by the existing studies involving CAM and mental health as most of the mental health studies found were of poor quality, and did not measure the quality of life of the participants or their feelings of empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary and alternative medicines (CAM) purportedly offer couples a way to improve outcomes and/or decrease stress and anxiety levels during treatment [ 2 4 ]. CAM are also used to incorporate cultural traditions of health and fertility as well as increase feelings of hope and control during a biomedicalized fertility treatment plan [ 5 ]. Some patients also use CAM as an alternative to assisted reproductive technologies, although most fertility patients use CAM in addition to biomedical fertility treatment [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cause of symptoms presented are also debated from the various models, it can be described as supernatural 8,26 and therefore requiring religious aid such as prayers and complementary treatments, or biomedical that may require medication or surgery. Read et al 27 researched into the use of complementary and alternative medicine by patients of various ethnicities in Canada, finding that many women endorsed the complementary and alternative medicine for infertility, focusing mainly on acupuncture and Chinese or other herbal medicines, as well as medicines that derived from their cultural backgrounds. This pursuit of their own culture's traditional healing methods may not be seen as acceptable or understandable by healthcare professionals in the dominant culture, 27 revealing the strong paternalistic and biomedical feature of some clinicians which may discourage patients from seeking healthcare.…”
Section: Multicultural Attitude To Healthmentioning
confidence: 99%
“…Read et al 27 researched into the use of complementary and alternative medicine by patients of various ethnicities in Canada, finding that many women endorsed the complementary and alternative medicine for infertility, focusing mainly on acupuncture and Chinese or other herbal medicines, as well as medicines that derived from their cultural backgrounds. This pursuit of their own culture's traditional healing methods may not be seen as acceptable or understandable by healthcare professionals in the dominant culture, 27 revealing the strong paternalistic and biomedical feature of some clinicians which may discourage patients from seeking healthcare. 28 Thus the act of introspection and deconstruction of a situation, by looking at the way in which human biology may be different e.g.…”
Section: Multicultural Attitude To Healthmentioning
confidence: 99%